The Study Of Dermatoglyphics Pattern In Females With Primary Infertility - Rauniyar, Shyambabu P.; Chimurkar, Vilas; Anjankar, Vaibhav P.; More, Akash (South Eastern European Journal of Public Health, 2024)
Background: Dermatoglyphics, the study of fingerprint ridge patterns, has been recognized for its potential in reflecting genetic and developmental variations. Primary infertility, defined as the inability to conceive after a year of regular, unprotected intercourse, is influenced by genetic, hormonal, and environmental factors. This study aims to investigate dermatoglyphic patterns in females with primary infertility to explore possible correlations between these patterns and infertility, providing insights for early diagnosis and management. Objective: The primary objective of this protocol is to systematically analyze dermatoglyphic patterns in females with primary infertility and compare them with those of fertile females. The study seeks to identify specific fingerprint characteristics that may serve as non-invasive markers for primary infertility. Methodology: This cross-sectional study will include two groups: females diagnosed with primary infertility and age-matched fertile controls. Dermatoglyphic data will be collected using the ink method, and the following parameters will be analyzed: total ridge count (TRC), patterns of arches, loops, and whorls, and other key qualitative features. Statistical analysis will be performed to evaluate significant differences between the two groups. Expected outcome: The study is expected to reveal distinct dermatoglyphic patterns in females with primary infertility compared to fertile females. Identifying such patterns may provide valuable markers for assessing genetic predispositions and could potentially assist in early diagnosis and personalized treatment strategies for infertility. Conclusion: This protocol outlines a method for studying the potential role of dermatoglyphic patterns in primary infertility, proposing a non-invasive, cost-effective diagnostic approach. Further research may help in establishing dermatoglyphics as a supplementary tool in infertility assessment and managemen.